Anganwadi based nutritional survey of children in Attappadi - Raju, K. K. Rakesh; Ajithkumar, V. T.; Ashraf, T. P.; Riyaz, A.; Cherian, N. C.; Rajagopalan, K. C.; Aravindan, K. P.; Govindraj, Geeta (International Journal of Contemporary Pediatrics, 2020)
Background: Malnutrition and anaemia form major public health problems among the school age children, particularly in the developing countries. Methods: A cross sectional study was conducted among children between 6 months and 18 years, in randomly selected 25 Anganwadis of Attappadi area. Objective of the study was to estimate the prevalence of anaemia and malnutrition among the children of Attappadi. Children were divided in to tribal and nontribal. Anthropometric measurements, haemoglobin estimation by cyanmethemoglobin method and peripheral smear examination were done. Results: 65.5% tribal and 54.1% non-tribal were anaemic. Among males 65.9% tribal and 56.4% non-tribal were anaemic. Among females 65.1% tribal and 52.6% nontribal were anaemic. In the age group less than 6 years, 9% tribal females, 8.9% nontribal females, 12% tribal males and 5.8% nontribal males were severely stunted. Above 6yrs it was 3.3% tribal females, 2.7% nontribal females, 2.4% tribal males and 7.4% nontribal males. In the age group less than 6 years, 12.5% tribal females, 3.9% nontribal females, 15.9% tribal males and 4.3% nontribal males had severe underweight. Above 6 years it was 8.3% tribal females, 0% non-tribal females, 19% tribal males and 3% non-tribal males. Conclusions: Anaemia and malnutrition are common among children of Attappadi. Tribal children are more affected than non-tribal children. Anaemia is more common among two age groups, less than 5 years and more than 11 years. Among females’ adolescent girls are more affected. Periodic assessment of growth parameters and early detection and treatment of anaemia are needed.